A Multidimensional Analysis of a High-Stakes English Listening Test: A Corpus-Based Approach - Tao, Xuelian; Aryadoust, Vahid (Education sciences, 2024)
The Gaokao, also known as China’s national college entrance exam, is a high-stakes exam for nearly all Chinese students. English has been one of the three most important subjects for a long time, and listening plays an important role in the Gaokao English test. However, relatively little research has been conducted on local versions of Gaokao’s English listening tests. This study analyzed the linguistic features and corresponding functional dimensions of the three different text types in the Gaokao’s listening test, investigating whether the papers used in three major regions of China were differentiated in terms of the co-occurrence patterns of lexicogrammatical features and dimensions of the transcripts. A corpus consisting of 170 sets of test papers (134,913 words) covering 31 provinces and cities from 2000 to 2022 was analyzed using a multidimensional analysis wherein six exclusive dimensions were extracted. The results showed that there were meaningful differences across short conversations, long conversations, and monologues with regard to the six dimensions’ scores, and regions further had significant differences in three dimensions: Syntactic and Clausal Complexity, Oral versus Literate Discourse, and Procedural Discourse, while Time Period was not associated with any differences. Implications for language teaching and assessment are discussed.